A Trispecific Anti-HIV Chimeric Antigen Receptor Containing the CCR5 N-Terminal Region - Hajduczki, Agnes; Danielson, David T.; Elias, David S.; Bundoc, Virgilio; Scanlan, Aaron W.; Berger, Edward A. (Frontiers in Cellular and Infection Microbiology, 2020)
Anti-HIV chimeric antigen receptors (CARs) promote direct killing of infected cells, thus offering a therapeutic approach aimed at durable suppression of infection emerging from viral reservoirs. CD4-based CARs represent a favored option, since they target the essential conserved primary receptor binding site on the HIV envelope glycoprotein (Env). We have previously shown that adding a second Env-binding moiety, such as the carbohydrate recognition domain of human mannose-binding lectin (MBL) that recognizes the highly conserved oligomannose patch on gp120, increases CAR potency in an in vitro HIV suppression assay; moreover it reduces the undesired capacity for the CD4 of the CAR molecule to act as an entry receptor, thereby rendering CAR-expressing CD8+ T cells susceptible to infection. Here, we further improve the bispecific CD4-MBL CAR by adding a third targeting moiety against a distinct conserved Env determinant, i.e. a polypeptide sequence derived from the N-terminus of the HIV coreceptor CCR5. The trispecific CD4-MBL-R5Nt CAR displays enhanced in vitro anti-HIV potency compared to the CD4-MBL CAR, as well as undetectable HIV entry receptor activity. The high anti-HIV potency of the CD4-MBL-R5Nt CAR, coupled with its all-human composition and absence of immunogenic variable regions associated with antibody-based CARs, offer promise for the trispecific construct in therapeutic approaches seeking durable drug-free HIV remission.